Contact Lie systems: theory and applications - Lucas, Javier de; Rivas, Xavier (Journal of Physics A: Mathematical and Theoretical, 2024)
A Lie system is a time-dependent system of differential equations describing the integral curves of a time-dependent vector field that can be considered as a curve in a finite-dimensional Lie algebra of vector fields V. We call V a Vessiot-Guldberg Lie algebra. We define and analyse contact Lie systems, namely Lie systems admitting a Vessiot-Guldberg Lie algebra of Hamiltonian vector fields relative to a contact manifold. We also study contact Lie systems of Liouville type, which are invariant relative to the flow of a Reeb vector field. Liouville theorems, contact Marsden-Weinstein reductions, and Gromov non-squeezing theorems are developed and applied to contact Lie systems. Contact Lie systems on three-dimensional Lie groups with Vessiot-Guldberg Lie algebras of right-invariant vector fields and associated with left-invariant contact forms are classified. Our results are illustrated with examples having relevant physical and mathematical applications, e.g. Schwarz equations, Brockett systems, quantum mechanical systems, etc. Finally, a Poisson coalgebra method to derive superposition rules for contact Lie systems of Liouville type is developed.
Keywords: lie system; superposition rule; contact manifold; coalgebra method; contact Marsden–Weinstein reduction; JCR; Scopus